Safeguarding Intangible Cultural Heritage: a photobook of traditional foodways of the Isukha and East Pokot communities of Kenya - Maundu, P.; Muiruri, P.; Adeka, R.; Ombonya, J.; Morimoto, Y.; Bosibori, E.; Kibet, S.; Odubo, A.; UNESCO Safeguarding Intangible Cultural Heritage (UNESCO, 2013)
This photobook presents the results of traditional foodways documentation conducted in Isukha and East Pokot communities of Kenya within the project ‘Safeguarding traditional foodways of two communities in Kenya’ executed by UNESCO Nairobi Office. The documentation was undertaken between 2008-2012 largely by pupils of primary schools in Isukha and East Pokot. The pupils received great assistance from their teachers, local project coordinators and the project team mainly consisting of staff from National Museums of Kenya, Bioversity International and the Department of Culture.